Marketing Strategy Analysis to Improve the Competitiveness of Rindi Rizqi Chips MSMEs in Nganjuk Regency - Diani, Vita Aprillia; Samari, Samari (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim : Analysis of marketing strategies applied to increase competitiveness in Rindi Rizqi Chips MSMEs in Nganjuk Regency. Design/Methode/Approach : This research was conducted using a qualitative approach through a case study. Data were collected through three main methods: observation, interviews, and documentation. The participant involved in this research include business owners, employees, and buyers of Rindi Rizqi MSMEs. Research Finding : This study found that Rindi Rizqi Chips MSMEs apply the 4P marketing strategy to improve competitiveness. Quality products without preservatives, competitive prices, distribution through modern stores, and promotion through bazaars and social media support increased visibility and customer loyalty. Excellence in quality, competitive pricing, and product uniqueness strengthen the position of MSMEs in the snack food industry. Theoretical contribution/Originality : This research enriches the literature on MSME marketing strategies by highlighting the application of the 4P marketing mix in improving competitiveness. The findings show how the elements of product, price, place, and promotion interact with each other to fulfill market needs and increase product visibility. Practitionel/Policy implication : This research enriches the literature on MSME marketing strategies by highlighting the application of the 4P marketing mix in improving competitiveness. The findings show how the elements of product, price, place, and promotion interact with each other to meet market needs and increase product visibility. Research limitation : This research has limitations because it only involved one MSME, Rindi Rizqi Chips, so the results may not be generalizable to other MSMEs. The research focus on marketing strategy and competitiveness also requires future research to involve more MSMEs and use diverse methods for a more comprehensive understanding